2017
DOI: 10.1097/bcr.0000000000000554
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nutritional Support of Burn Service Patients by Increasing the Number of Days When 100% of Prescribed Formula Is Given

Abstract: The authors sought to increase the number of days when burn service patients receive 100% of prescribed enteral nutrition. The authors first performed a retrospective review of 37 patients (group 1) receiving enteral nutrition. The authors then created and implemented a nurse-directed feeding algorithm, placing patients into three age groups addressing maximum hourly infusion rates, high residual limits, initiating feeding, refeeding residuals, and replacing formula. The authors then performed a prospective re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
6

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
0
5
0
6
Order By: Relevance
“…There is also an opportunity to examine clinical practice and policies related to continuing EN feeding for tracheostomy and ventilated patients as recommended by Rousseau and others. 18,20 Limitations First, the cross-sectional nature of this study and the small sample size limit the extent to which we can generalize findings. Second, due to technical issues with the metabolic cart, it was not always available to measure caloric needs, and, in some cases, the predictive equation alone was used to establish caloric requirements.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…There is also an opportunity to examine clinical practice and policies related to continuing EN feeding for tracheostomy and ventilated patients as recommended by Rousseau and others. 18,20 Limitations First, the cross-sectional nature of this study and the small sample size limit the extent to which we can generalize findings. Second, due to technical issues with the metabolic cart, it was not always available to measure caloric needs, and, in some cases, the predictive equation alone was used to establish caloric requirements.…”
Section: Discussionmentioning
confidence: 95%
“…There is also an opportunity to examine clinical practice and policies related to continuing EN feeding for tracheostomy and ventilated patients as recommended by Rousseau and others. 18,20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean duration of EN interruptions was 8.9 ± 3 h/d . Conrad found in his study of burn patients that 100% of estimated nutrient needs were only met on an average of 59.9% of days when EN support was ordered . Nutrition and clinical outcomes can be compromised with prolonged inadequate nutrition support .…”
Section: Discussionmentioning
confidence: 99%
“…10 Conrad found in his study of burn patients that 100% of estimated nutrient needs were only met on an average of 59.9% of days when EN support was ordered. 29 Nutrition and clinical outcomes can be compromised with prolonged inadequate nutrition support. 12,13 Rimdeika et al demonstrated in adult burn patients who received <30 kcal/kg of nutrition/d a significantly higher association with increased complication rates, duration of treatment, and mortality (P < 0.05; P = 0.01; P < 0.01).…”
Section: Discussionmentioning
confidence: 99%